A method of GC-MS analysis of serum metabolites - Soheili, Masoud; Arefi Oskuei, Afsaneh; Rezaei Tavirani, Mostafa; Banitaba, Seyyed Mojtaba; Aliakbarzadeh, Ghazaleh; Salami, Mahmoud (Archives of Advances in Biosciences, 2017)
Metabolites are the intermediate and natural low molecular weight products of metabolic reactions that naturally occur within cells. Metabolomics is a post-genomics study that analyzes metabolic profile in all biological samples. Gas chromatography-mass spectrometry (GC-MS) is a powerful technique that detects volatile components. In this study we evaluate the metabolite profile of serum with a simple method for derivatization. The metabolic profile of serum taken from 16 rats was analyzed using GC-MS after protein precipitation with acetonitrile. Then, it was derivatized with a method requiring the less number and volume of materials. Acquisition chromatograms were pre-processed and analyzed using National Institute of Standards and Technology (NIST) library. We detected 35 metabolites with probability of >60% perfect match according to spectrum fragments analysis by NIST library.This study represents the metabolome profile of serum instead the change of metabolites that can be evaluated by a simple derivatization method.